Lumbar Intervertebral Discal Cyst: A Rare Cause of Low Back Pain and Radiculopathy. Case Report and Review of the Current Evidences on Diagnosis and Management - Certo, Francesco; Visocchi, Massimiliano; Borderi, Alessandro; Pennisi, Claudia; Albanese, Vincenzo; Barbagallo, Giuseppe M. V. (Evidence-Based Spine-Care Journal, 2014)
Study Design Case Report and review of the literature.Objective The objective of the article is to report an illustrative case successfully treated by microsurgery and to review the literature on the current evidence on diagnosis and management of lumbar discal cysts.Methods A 43-year-old male patient presented with severe back pain, radiating down to the right leg, as well as with paraesthesias in the right L3 and L4 dermatomes. Magnetic resonance imaging of the lumbar spine revealed an intraspinal, extradural space-occupying lesion at the L3–L4 disc level, causing compression of the neural structures. The lesion was surgically removed and a diagnosis of lumbar discal cyst was made. Postoperatively, symptoms improved and the patient was discharged with no complications. A systematic review of pertinent articles published up to February 2014 was performed. Key articles were searched to identify studies describing the diagnosis and management modalities of lumbar discal cysts and the comparative effectiveness and safety of microsurgery versus endoscopic treatment.Conclusions Discal cysts are rare causes of low back pain and radiculopathy. Few cases have been reported; however, conclusive information about their natural history is not available and the best mode of treatment remains controversial. We submit that lumbar intervertebral disc cysts, with their peculiar radiological and anatomic features, should be considered in the differential diagnosis among rare causes of low back pain and radiculopathy.
Keywords: discal cyst; discography; intervertebral disc; intraspinal cyst; lumbar spine